Modelo de introdução de competências individuais para projetos de implementação da indústria 4.0 - Prado, Rogério Glaser (2021)
The arrival of industry 4.0 shows a new way to achieve the best results in companies, but scarce scientific studies address the skills necessary for the workforce to prepare to operationalize it. This study aims to present a model of implementation of hard and soft competencies for industry projects 4.0. The methodology used was the literature review to identify these competencies followed by consultation with specialists using the Delphi method. The result was the proposition of a model of implementation of hard and soft competencies endorsed by experts, a theoretical contribution to studies of Industry 4.0, contributing to advances in technology management and innovation.